2022
DOI: 10.3390/children9111783
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions (ADRs) of Montelukast in Children

Abstract: Montelukast is a leukotriene receptor antagonist (LTRA) commonly prescribed for asthma, allergic rhinitis and sleep-related breathing disorders. Recently, some studies have reported several adverse events, such as neuropsychiatric disorders and sleep disturbances, among children. Objective: To obtain more insight into the safety profile of montelukast for children with asthma, allergic rhinitis and sleep-related breathing disorders. Method and results: We retrospectively studied all adverse drug reactions to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
1
2
0
1
Order By: Relevance
“…In another similar study in the literature, the most frequently observed neuropsychiatric effects after montelukast treatment were reported as irritability, aggressive behavior, and sleep disorders [ 24 ]. In a different study conducted in children in the literature, sleep problems and agitation were observed most frequently after the use of montelukast, similar to our study [ 35 ]. According to the literature and our study, the most common neuropsychiatric effects seen with the use of montelukast in children are similar.…”
Section: Discussionsupporting
confidence: 90%
“…In another similar study in the literature, the most frequently observed neuropsychiatric effects after montelukast treatment were reported as irritability, aggressive behavior, and sleep disorders [ 24 ]. In a different study conducted in children in the literature, sleep problems and agitation were observed most frequently after the use of montelukast, similar to our study [ 35 ]. According to the literature and our study, the most common neuropsychiatric effects seen with the use of montelukast in children are similar.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we screened all NEs associated with montelukast and found that headache was the most common NE in all RCT studies, although our analysis did not reveal a relationship between NE and montelukast. In addition, the high incidence of such NEs among adults and children in the United States, Canada, and Europe [ 37 ] suggests that montelukast may lead to NEs. Consequently, montelukast-associated NEs have drawn much attention from practicing pediatricians in the United States, Australia, and the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Issues with the safety profile of montelukast are well-documented; sleep disturbance, agitation and behavioural disturbance have been reported,11 but the prevalence of adverse effects varies widely in the literature (0%–31.9%)1 3 4 11; while the wide range of reported prevalence of adverse effects may be attributable to study design and follow-up, the indication, dose and duration of treatment, as well as the use of montelukast as a supplemental or primary treatment may also be of relevance. Systematic reviews of montelukast use in OSA have a paucity of information regarding its safety profile, although nausea and headaches have been reported 12.…”
Section: Commentarymentioning
confidence: 99%